2021
DOI: 10.21203/rs.3.rs-434116/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

TLK1-MK5 axis drives prostate cancer cell motility and pathologic features of aggressiveness

Abstract: Background: Majority of prostate cancer (PCa) related fatalities occur due to metastasis of cancer cells to adjacent and distal organs. We identified the novel interaction between two kinases (TLK1-MK5) that in part may initiate a signaling cascade promoting PCa metastasis. In PCa, TLK1-MK5 signaling might be crucial as androgen deprivation therapy leads to increased expression of TLK1 and compensatory activation of MK5 in metastatic castration-resistant prostate cancer patients. Methods: We performed scratch … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The cell proliferation assay was conducted, as previously described [ 30 ]. Briefly, 2000 cells/well were seeded in a 96-well plate, with 10% FCS containing media with or without different concentrations of J54.…”
Section: Methodsmentioning
confidence: 99%
“…The cell proliferation assay was conducted, as previously described [ 30 ]. Briefly, 2000 cells/well were seeded in a 96-well plate, with 10% FCS containing media with or without different concentrations of J54.…”
Section: Methodsmentioning
confidence: 99%
“…However, studies aimed at identifying TLKs' role in prostate cancer progression and drug resistance are very limited. Notably, the TLK1 gene was identified by co-expression analysis using WGCNA as a key driver of PCa, highly enriched among candidate genes collected from expression Quantitative Trait Loci, somatic copy number alterations and prognostic analyses [28] . We also recently observed from data mining that TLK1 expression at mRNA level is increased in metastatic and high grade prostatic adenocarcinoma compared to the low risk tumors [29] .…”
Section: The Mammalian Tousled Like Kinases and Translational Upregulation Of Tlk1bmentioning
confidence: 99%
“…Furthermore, ADT increases pMK5 S354 level in LNCaP cells, and this pMK5 protein is progressively increased in tumors of higher grades and nodal metastatic scores analyzed from TRAMP mice prostate tissue and human PCa TMA, suggesting that the TLK1>MK5 signaling may be associated with increased aggressiveness of PCa. Finally, disruption of TLK1>MK5 axis by TLK1 or MK5 inhibition drastically reduces PCa cells motility analyzed in a panel of PCa cell lines [ 29 ] . Figure 1 graphically depicts the currently known multifaceted roles of TLK1 in mCRPC progression and acquisition of drug resistance.…”
Section: Role Of Tlk1 In Other Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously demonstrated that a serine/threonine (S/T) protein kinase, Tousled-like kinase 1 (TLK1) could promote PCa cell motility and clinical aggressiveness by phosphorylating another S/T kinase, MAPK-activated protein kinase 5 (MAPKAPK5/MK5) (7,8). TLK1 is known as a genome maintenance regulator, which functions in regulating replication, transcription, cell cycle checkpoint control, DNA damage response and repair through its direct and indirect substrates (reviewed in (9)(10)(11)(12)).…”
Section: Introductionmentioning
confidence: 99%